2014
DOI: 10.1007/s00127-014-0860-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of suicide according to level of psychiatric treatment: a nationwide nested case–control study

Abstract: Psychiatric admission in the preceding year was highly associated with risk of dying from suicide. Furthermore, even individuals who have been in contact with psychiatric treatment but who have not been admitted are at highly increased risk of suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 28 publications
3
70
0
1
Order By: Relevance
“…This risk varies across different clinical populations, with psychiatric inpatients showing the highest risk of suicide within the next year. 13 The risk of suicide seems to be greatest during the first few months after diagnosis across all mental disorders. [16][17][18] The risk of suicide is also influenced by treatment factors, which will be described later in the review.…”
Section: Epidemiologymentioning
confidence: 99%
“…This risk varies across different clinical populations, with psychiatric inpatients showing the highest risk of suicide within the next year. 13 The risk of suicide seems to be greatest during the first few months after diagnosis across all mental disorders. [16][17][18] The risk of suicide is also influenced by treatment factors, which will be described later in the review.…”
Section: Epidemiologymentioning
confidence: 99%
“…Overall, psychiatric inpatients have a rate of 147 suicides per 100,000 patient-years [14], which is almost 13 times higher than the annual global age-standardized suicide rate of 11.4 per 100,000, provided by the World Health Organization (WHO) [25]. While acknowledging that not all people with mental disorders receive treatment, a recent study found that the risk of suicide varies according to the level of mental health care received; people admitted as psychiatric inpatients within the last year had a 44-fold higher risk of suicide than the general population, whereas those receiving outpatient care or psychiatric medication had an 8- or 6-fold higher risk, respectively [15]. It would probably be wrong to conclude that the treatment causally increases risk of suicide; presumably, effective treatment would decrease the risk of suicide compared to a scenario in which that person did not receive treatment.…”
Section: Relative Riskmentioning
confidence: 99%
“…The risk of suicide in psychiatric patients varies over time, and an excessive risk of suicide has been found in patients who are currently admitted or who have been recently discharged from a psychiatric hospital [14,15,16,17]. Although suicides among hospitalised psychiatric patients are rare, it is considered to be a public health problem [18].…”
Section: Introductionmentioning
confidence: 99%
“…Observational cohort studies have also produced inconsistent results regarding the association of both medical and psychiatric inpatient admission with risk of repeat self-harm and suicide [12, 13]. However, a recent study suggested psychiatric admission in particular may be associated with an increased risk of suicide [14]. These data have led to the suggestion that this association may be causal [15], but the limitations of confounding that are inherent in observational analysis mean these results are difficult to interpret [16].…”
Section: Introductionmentioning
confidence: 99%